Long–Term Disease Control After Allogeneic Hematopoietic Stem Cell Transplantation in Primary Cutaneous T–Cell Lymphoma; Results From a Single Institution Analysis - Dimitriou, Florentia; Schanz, Urs; Nair, Gayathri; Kimeswenger, Susanne; Brüggen, Marie-Charlotte; Hoetzenecker, Wolfram; French, Lars E.; Dummer, Reinhard; Cozzio, Antonio; Guenova, Emmanuella (Frontiers in Medicine, 2020)
Background Allogeneic hematopoietic stem cell transplantation (alloHSCT) has been proposed as curative approach for advanced cutaneous T – cell lymphomas (CTCL). Currently, there is no established consensus for the management of disease relapse after alloHSCT. Results Ten patients, previously treated with multiple lines of systemic treatment, received alloHSCT. Six patients had achieved partial response (PR, N = 5) and complete response (CR, N = 1) prior to HSCT. Post – HSCT, seven patients (N = 7) relapsed after a median time of 3.3 months (0.5 – 7.4 months) and were subsequently treated with radiotherapy (RT, N =1), RT and adoptive T-cell transfer with EBV specific cells (N =1), R-CHOP (N = 1) and interferon alpha - 2a combined either with donor lymphocyte infusion (N = 1) or with brentuximab – vedotin (N = 1). One patient (N = 1) achieved PR only after reducing the immunosuppression. Two patients relapsed again and received interferon alpha - 2a and brentuximab – vedotin, respectively. After a median follow-up time of 12.6 months (3.5 – 73.7 months) six patients were alive (60%) and four had deceased, three (N = 3) due to CTCL and one (N = 1) due to GVHD. Conclusion Disease relapse after alloHSCT can be controlled with available treatments. For most patients who ultimately relapsed, reduction of immunosuppression and interferon alpha - 2a either administered alone or in combination with another systemic agent were preferred. Although interferon alpha – 2a, similarly to immunosuppression reduction, may be beneficial for the achievement of graft – versus – lymphoma effect, the risk of simultaneous worsening of GVHD must be carefully evaluated and taken into consideration